CIA. Molinera La Encantada - Mendiola, Alfredo (2004)
The present case raises the general situation of a hypothetical company well positioned in the market and that apparently operates efficiently. The focus is on the short-term financial management policy that, at first glance, does not seem to present major drawbacks. However, in-depth analysis can lead to different conclusions.